2019
DOI: 10.1055/s-0037-1611812
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Organic Photochemical Reactions in the Absence of External Photocatalysts

Abstract: Visible-light-driven organic photochemical reactions have attracted substantial attention from the synthetic community. Typically, catalytic quantities of photosensitizers, such as transition metal complexes, organic dyes, or inorganic semiconductors, are necessary to absorb visible light and trigger subsequent organic transformations. Recently, in contrast to these photocatalytic processes, a variety of photocatalyst-free organic photochemical transformations have been exploited for the efficient formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(48 citation statements)
references
References 59 publications
0
47
0
1
Order By: Relevance
“…Until the past few years, EDA-complex photochemistry has attracted more and more chemists and provided new opportunities for synthetic chemistry [ 8 ]. Moreover, diverse photocatalyst-free photochemical reactions have been employed to construct carbon–carbon and carbon–heteroatom bonds [ 9 ]. Among these methods, the product formations by aid of EDA complexes are the simplest and most rapid way.…”
Section: Reviewmentioning
confidence: 99%
“…Until the past few years, EDA-complex photochemistry has attracted more and more chemists and provided new opportunities for synthetic chemistry [ 8 ]. Moreover, diverse photocatalyst-free photochemical reactions have been employed to construct carbon–carbon and carbon–heteroatom bonds [ 9 ]. Among these methods, the product formations by aid of EDA complexes are the simplest and most rapid way.…”
Section: Reviewmentioning
confidence: 99%
“…6b On the other hand, the ability of some iminium ion intermediates to directly participate in the photoexcitation of substrates upon light excitation can realize previously inaccessible photocatalytic reactions without an additional photocatalyst. 24 Meanwhile, the chiral amine catalyst ensures effective stereochemical control of these reactions. As a result, this iminium ion activation mode allows the asymmetric -functionalization of unsaturated carbonyl compounds, leading to chiral -functionalized carbonyl compounds.…”
Section: Short Review Synthesis 3 Enantioselective Radical Functionalmentioning
confidence: 99%
“…were employed in photocatalytic oxidative or reductive transformations [8a,b] . On the other hand, photocatalyst‐free processes have also been exploited in which the reaction substrates can absorb light energy or generate an electron donor‐acceptor (EDA) complex [8c] to promote the chemical transformations in the absence of external photocatalysts [8d] . Although there are several related reviews were reported in the field of indoles synthesis including photocatalyzed reactions [9] .…”
Section: Introductionmentioning
confidence: 99%